KESADARAN PERPAJAKAN, SANKSI PAJAK DAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK - Hartono, Rudi; Yusran, Rio Rahmat (SCIENTIA JOURNAL, 2019)
Taxes are one source of state revenue comes from the people, which will be used to build the facilities needed by the community. Once the magnitude of the needs of the State, it was the tax revenue every year is not so encouraging, because it does not achieve the desired targets. This studyy aims to determine the effect of tax awareness, tax penalties and tax This study used a simple random sampling,using the formula solvin, there are 100 samples were examined and treated by using SPSS software version20.The hypothesis will be tested by t test and F test with a significance level of 10%. From the test results indicate that the F count (2,313)> F table (2,14). From the test t test shows a partial awareness of taxation positive and significant impact on tax compliance, with a value of F count> t table (1,894> 1,661), the sanction tax positive effect on tax compliance, with the value of t count (0.966)> t table (1,661), and the tax amnesty is not a positive effect on tax compliance with t count (1,195)> t table (1,661). From the result of determination (R 2 )0,067, which means awareness of taxation, tax penalties and tax amnesty has the effect of 6,7 percent on tax compliance. Referring to the results, we can conclude that the awareness of taxation, tax penalties and tax amnesty has a role in the increased tax and compliance in Indonesia.